Latihan Aktivitas Fisik Seperti Berjalan Setiap Hari pada Pasien Hipertensi - Koharuddin Koharuddin; Riri Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of walking physical activity on blood pressure in hypertension patients. This type of research is a systematic review, by reviewing several journals from the University of Indonesia library through CINAHL, Pubmed, Ebscohost, Springers, Wiley, and Scopus. The results of research from 11 literature searches that walking activity exercises can effectively reduce blood pressure levels, ranging from 6 minutes to 120 minutes per day, and 1200 minutes every week, can produce a better effect in hypertensive patients - the average decrease in SBP is significant between 2.6 mmHg and 22.6 mmHg. In conclusion, walking activity exercises are very useful and effective in reducing blood pressure levels, especially in hypertensive patients. Keywords: Physical Activity, Walking, Hypertension, Brisk Walking, Jogging